FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BERWIRAUSAHA PADA SISWA KELAS XII SMK NEGERI 1 KANDEMAN KABUPATEN BATANG TAHUN 2011/2012 - Aprilia, Fitriani (Universitas Negeri Semarang, 2012)
Interest in entrepreneurship is an encouragement, a sense of interest and the availability of the individual to conduct a business without fear of the risk will occur. Secondary vocational schools are educational institutions that prepare students to be a human resources that ready to work and have capacity for work independently (entrepreneurial) after graduate from this school. Factors originating from within the students and the factors that originate from outside is affecting interest in entrepreneurship. In this study population is 287 students. The samples are 74 students conducted by proportional random sampling. Independent variables exam-ined in this study were internal factors (X1) and external factors (X2). While the dependent variable is the interest in entrepreneurship (Y). The data was collected by questionnaires and documentation. The results of descriptive research showed that the percentage of interest in entrepreneurship is included in the high category, internal and external factors are included in either category. Partial internal factors have a significant influence of 28.84%, while external factors also have a significant effect of 7.34%. Variables simultaneously internal and external factors affect the interest of entrepreneurship by 48.4%